THE EFFECT OF LEVERAGE, BOARD OF DIRECTORS, AUDIT COMMITTEE AND COMPANY SIZE ON THE LEVEL OF HEALTH FINANCIAL PERFORMANCE - Utami, Martiana Riawati; Priantinah, Denies (Nominal: Barometer Riset Akuntansi dan Manajemen, 2019)
Abstract : The Effect Of Leverage, Board Of Directors, Audit Committee And Company Size On The Level Of Health Financial Performance. This research aims to analyze (1) the effect of Leverage on the Level of Health Financial Performance, (2) the effect of Board of Directors on the Level of Health Financial Performance, (3) the effect of Audit Committee on the Level of Health Financial Performance, (4) the effect of Company Size on the Level of Health Financial Performance, and (5) the effect of Leverage, Board of Directors, Audit Committee and Company Size simultaneously on the Level of Health Financial Performance. This research was a causal research. The population of this research are manufacturing companies listed in Indonesia Stock Exchange period 2014-2016. A purposive sampling method was used as a sampling method and 96 companies were selected as sample of research. The data analysis techniques were simple linear regression analysis and multiple linear regression analysis. The result of this research indicates that (1) Leverage has a positive effect on the Level of Health Financial Performance, (2) Board of Directors has a positive effect on the Level of Health Financial Performance, (3) Audit Committee has a positive effect on the Level of Health Financial Performance, (4) Company Size has a positive effect on the Level of Health Financial Performance, and (5) Leverage, Board of Directots, Audit Committee and Company Size simultaneously has a positive effect on the Level of Health Financial Performance. Keywords: Level of Health Financial Performance, Leverage, Board of Directors, Audit Committee, Company Size